2006
DOI: 10.1161/01.atv.0000229665.78997.0b
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Converts Human Macrophages Into Triglyceride-Loaded Foam Cells

Abstract: Objectives-Atherosclerotic lesions have regions that are hypoxic. Because the lesion contains macrophages that are loaded with lipid, we investigated whether hypoxia can influence the accumulation of lipids in these cells. Methods and Results-Exposure of human macrophages to hypoxia for 24 hours resulted in an increased formation of cytosolic lipid droplets and an increased accumulation of triglycerides. Exposure of the macrophages to oxidized low-density lipoprotein (oxLDL) increased the accumulation of cytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
125
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(140 citation statements)
references
References 32 publications
13
125
1
1
Order By: Relevance
“…5C); however, both studies found increased lactate production (Fig. 6B) (56). We noted at least at the gene level that, relative to the less differentiated monocytes isolated straight from blood, glycolytic enzymes were up-regulated in MDM to some extent even in normoxic conditions (Figs.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…5C); however, both studies found increased lactate production (Fig. 6B) (56). We noted at least at the gene level that, relative to the less differentiated monocytes isolated straight from blood, glycolytic enzymes were up-regulated in MDM to some extent even in normoxic conditions (Figs.…”
Section: Discussionmentioning
confidence: 62%
“…One of the macrophage lineage populations examined above and that is widely used as an in vitro model for human macrophages, namely MDM, does not require an exogenous CSF for survival under aerobic conditions and therefore is not suitable to study any prosurvival activity of hypoxia (46,55,56). Others have found that hypoxia increased Glut1 mRNA levels in MDM and speculated that this change could be important for macrophage survival in hypoxic diseased tissue (54).…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1 activates genes responsible for switching from oxidative to glycolytic metabolism such as the ones coding for glucose transporters, glycolytic enzymes, lactate dehydrogenase and pyruvate dehydrogenase kinase 1 (Majmundar et al, 2010). Furthermore, hypoxia has been shown to stimulate lipid storage and inhibit lipid catabolism in cultured cardiac myocytes and macrophages (Boström et al, 2006;Huss et al, 2001), but the involvement of HIFs in these processes was not investigated. More recent studies using transgenic mice have suggested that artificial or diet induced activation of liver HIF signalling can augment lipid accumulation by modifying hepatocyte lipid metabolism (Kim et al, 2006;Nath et al, 2011;Qu et al, 2011;Rankin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…HIF-induced transcription promotes angiogenesis, erythropoiesis, metastasis and metabolic reprogramming, such as shifting cell metabolism from oxidative phosphorylation to glycolysis. HIF activation due to hypoxia or loss of VHL function also reprograms lipid metabolism leading to lipid accumulation (Huss et al, 2001;Boström et al, 2006;Rankin et al, 2009;Kucejova et al, 2011;Qu et al, 2011;Walter et al, 2014).…”
Section: Mitochondria As Redox Signaling Nodesmentioning
confidence: 99%